Development of a Competence-Based Spine Surgery Fellowship Curriculum Set of Learning Objectives in Canada. Issue 6 (March 2016) - Larouche, Jeremie; Yee, Albert J. M.; Wadey, Veronica; Ahn, Henry; Hedden, Douglas M.; Hall, Hamilton; Broad, Robert; Bailey, Chris; Nataraj, Andrew; Fisher, Charles; Christie, Sean; Fehlings, Michael; et al.
Abstract : Study Design: Modified-Delphi expert consensus method. Objective: The aim of this study was to develop competence-based spine fellowship curricula as a set of learning goals through expert consensus methodology in order to provide an educational tool for surgical educators and trainees. Secondarily, we aimed to determine potential differences among specialties in their rating of learning objectives to defined curriculum documents. Summary of Background Data: There has been recent interest in competence-based education in the training of future surgeons. Current spine fellowships often work on a preceptor-based model, and recent studies have demonstrated that graduating spine fellows may not necessarily be exposed to key cognitive and procedural competencies throughout their training that are expected of a practicing spine surgeon. Methods: A consensus group of 32 spine surgeons from across Canada was assembled. A modified-Delphi approach refined an initial fellowship-level curriculum set of learning objectives (108 cognitive and 84 procedural competencies obtained from open sources). A consensus threshold of 70% was chosen with up to 5 rounds of blinded voting performed. Members were asked to ratify objectives into either a general comprehensive or focused/advanced curriculum. Results: Twenty-eight of 32 consultants (88%) responded and participated in voting rounds. Seventy-eight (72%) cognitive and 63 (75%) procedural competency objectives reached 70% consensus in the first round. This increased to 82 cognitive and 73 procedural objectives by round 4. The final curriculum document evolved to include a general comprehensive curriculum (91 cognitive and 53 procedural objectives), a focused/advanced curriculum (22 procedural objectives), and a pediatrics curriculum (22 cognitive and 9 procedural objectives). Conclusion: Through a consensus-building approach, the study authors have developed a competence-based curriculum set of learning objectives anticipated to be of educational value to spine surgery fellowship educators and trainees. To our knowledge, this is one of the first nationally based efforts of its kind that is also anticipated to be of interest by international colleagues. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text